Onocerin Biosynthesis Requires Two Highly Dedicated Triterpene Cyclases in a Fern Lycopodium clavatum. (28th January 2016) - Araki, Takeshi; Saga, Yusuke; Marugami, Momo; Otaka, Junnosuke; Araya, Hiroshi; Saito, Kazuki; Yamazaki, Mami; Suzuki, Hideyuki; Kushiro, Tetsuo
Abstract: Onocerin is known for its unusual structure among triterpenoids, with a symmetrical structure that is formed by cyclizations at the both termini of dioxidosqualene. The nature of the enzyme catalyzing these unusual cyclizations has remained elusive for decades. Here, we report the cloning of genes responsible for these reactions; they exhibited unprecedented substrate specificities among oxidosqualene cyclase family members. Two genes, LCC and LCD, were identified from the fern Lycopodium clavatum . Expression in yeast revealed that both were required to produce α‐onocerin. LCC, the first dioxidosqualene cyclase, catalyzed the production of a novel intermediate pre‐α‐onocerin from only dioxidosqualene as a substrate; LCD catalyzed the second half of the cyclization, exclusively from pre‐α‐onocerin. These results demonstrated that these two most unusual oxidosqualene cyclases were involved in onocerin biosynthesis. Abstract : Cyclize from both ends : A symmetrical triterpenoid α‐onocerin was found to require two enzymes for its biosynthesis. Both exhibited unprecedented substrate specificity among oxidosqualene cyclases, one specific to dioxidosqualene and the other to partially cyclized pre‐α‐onocerin.